Pengaruh Manajemen Keragaman Tenaga Kerja dan Employee Engagement terhadap Turnover Intention pada Karyawan PT Hindoli - Vina Vira Febrisa; Zunaidah Zunaidah; Isni Andriana (Institut Agama Islam Nasional Laa Roiba Bogor, 2023)
This study aims to determine and analyze the effect of workforce diversity management and employee engagement on turnover intention at PT. Hindoli. The study uses quantitative data type by using questionnaires. The sampling in this study uses the nonprobability sampling with a sample of 178 respondents. The analysis technique used is Structural Equation Model (SEM). The results showed that workforce diversity management had a negative and significant effect on turnover intention, employee engagement had a negative and significant effect on turnover intention, and employee engagement had a more dominant effect on turnover intention.